New management approches in construction - Mastura Jaafar; Abdul Rashid Abdul Aziz (Academic imprint series, 2013)
The book goes on to explore the strategic management and project management approaches of business and project entities in construction. Knowledge and ideas discussed in this book were contributed by scholars who are closely involved with research in the industry. Having read their ideas, improving performance would be a significant contribution of this book to the existing and future industry players in construction.